2021
DOI: 10.1101/2021.07.20.453075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription factor regulation of eQTL activity across individuals and tissues

Abstract: Tens of thousands of genetic variants associated with gene expression ( cis -eQTLs) have been discovered in the human population. These eQTLs are active in various tissues and contexts, but the molecular mechanisms of eQTL variability are poorly understood, hindering our understanding of genetic regulation across biological contexts. Since many eQTLs are believed to act by altering transcription factor (TF) binding affinity, we hypothesized that analyzing eQTL effect size as a function of TF level may allow … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Regulatory features like transcription factors and chromatin markers play vital roles in gene expression regulation and have been reported to be effective in associating eQTLs with target genes[25, 26]. In other words, in the sequence between non-coding mutations and the TSS, regulatory feature regions will provide more information for eQTLs sign prediction compared to other regions.…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory features like transcription factors and chromatin markers play vital roles in gene expression regulation and have been reported to be effective in associating eQTLs with target genes[25, 26]. In other words, in the sequence between non-coding mutations and the TSS, regulatory feature regions will provide more information for eQTLs sign prediction compared to other regions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, blood-based gene expression levels of other genes were used previously to identify context dependent effects 18 , some of which were related to type 1 interferon signaling. A recent study using the GTEx dataset also revealed context dependent eQTLs that could be attributed to transcript factor levels 19 . The limitations of these methods are that not all confounding contexts might be known or easily measurable, and that individual (gene expression) measurements might not be perfect proxies for specific contexts, and thus can be noisy: for instance, cell type quantifications can differ, depending on the used technology and gate settings whereas measured expression levels of specific genes are unlikely to perfectly reflect environmental stimuli or transcription factor activity.…”
Section: Introductionmentioning
confidence: 99%